The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1061/(asce)me.1943-5479.0000115
|View full text |Cite
|
Sign up to set email alerts
|

Lean Transformation in a Modular Building Company: A Case for Implementation

Abstract: Encouraged by the remarkable productivity improvements in the manufacturing sector, the construction industry has a long history of trying to garner the benefits of manufacturing technologies. Whereas industrialized construction methods, such as modular and manufactured buildings, have evolved over decades, core techniques used in prefabrication plants vary only slightly from those employed in traditional site-built construction. The objective of this research was to develop and implement a production system f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 9 publications
0
54
0
11
Order By: Relevance
“…No caso de Yu et al (2013), as duas decisões eram inter-relacionadas. Quando o fluxo de produção de porta-a-porta foi olhado em relação a um fluxo de valor, o mapeamento só podia ser feito a nível da estação, já que um único mapa que, abrange todas as tarefas realizadas dentro de cada estação, seria ruim para manusear.…”
Section: Implementaçãounclassified
See 2 more Smart Citations
“…No caso de Yu et al (2013), as duas decisões eram inter-relacionadas. Quando o fluxo de produção de porta-a-porta foi olhado em relação a um fluxo de valor, o mapeamento só podia ser feito a nível da estação, já que um único mapa que, abrange todas as tarefas realizadas dentro de cada estação, seria ruim para manusear.…”
Section: Implementaçãounclassified
“…O problema com o mapeamento a este nível é que fluxo de valor pode não ser estável. Para este estudo, Yu et al (2013) relata que mapas em dois níveis foram usados simultaneamente para a identificação de desperdícios e desenvolvimento de soluções.…”
Section: Implementaçãounclassified
See 1 more Smart Citation
“…Lean production principles, which first emerged in the Japanese manufacturing industry, are a collection of practices that aim to increase productivity, maximize value, and minimize waste [15]. While the application of lean principles in modular construction can significantly improve project performance [16][17][18], there still exists some key challenges with respect to the dichotomy between design and construction. For instance, Sarhan and Fox [19] found that in lean construction, there is often a conflict border between design and construction, resulting in inaccurate designs, rework, lack of constructability, and final products with significant variation from specified design values.…”
Section: Production Optimization Methods In Modular Constructionmentioning
confidence: 99%
“…Also included on the site is a small shopping area/food court, and a preexisting historic structure on the site will be refurbished as a Center of Entrepreneurship co-working space. The founder of the Makerhoods project (second author of this paper) is a long-time advocate and practitioner of Lean Management (Manrique et al 2007;Yu et al 2013), and thus he naturally sought to pursue the implementation of Lean concepts and paradigms in this new venture. Given the constraints that prevailing rental rates in the target area placed on the construction budget, the potential cost reduction from a less wasteful and more productive construction process (i.e.…”
Section: Introductionmentioning
confidence: 99%